2018
DOI: 10.4293/jsls.2017.00070
|View full text |Cite
|
Sign up to set email alerts
|

Robotic TAPP Ventral Hernia Repair: Early Lessons Learned at an Inner City Safety Net Hospital

Abstract: Background and Objectives:Ventral hernia repair is one of the most commonly performed general surgery procedures, and minimally invasive approaches are increasingly preferred. The physiologic repair offered by the preperitoneal approach is favorable, with reduced complications, but it remains a technical challenge. The robotic platform allows for enhanced instrument flexibility and ease of operation. We conducted a retrospective review of our experience with robotic transabdominal preperitoneal repair (rTAPP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Finally, Kennedy et al compared 27 rIPOM to 36 rTAPP patients. Operative time was similar between groups, as were minor perioperative complications [37]. No inferences can be drawn regarding hernia recurrence due to lack of longterm follow-up.…”
Section: Recommendaɵons: Rtappmentioning
confidence: 83%
“…Finally, Kennedy et al compared 27 rIPOM to 36 rTAPP patients. Operative time was similar between groups, as were minor perioperative complications [37]. No inferences can be drawn regarding hernia recurrence due to lack of longterm follow-up.…”
Section: Recommendaɵons: Rtappmentioning
confidence: 83%
“…In a total of 11 studies with 2320 patients, 1353 patients who underwent minimally invasive VHR with intraperitoneal mesh placement and 967 patients who underwent minimally invasive VHR with extraperitoneal mesh placement were included in the qualitative synthesis and quantitative synthesis (Fig. 1) [10,11,[14][15][16][17][18][19][20][21][22]. All patients had similar baseline characteristics (Table 1).…”
Section: Search Resultsmentioning
confidence: 99%
“…A total 8 studies (866 patients) reported readmission rates (Fig. 2d) [14,15,[17][18][19][20][21][22]. A total of 1 study reported that patients in both groups were not readmitted during the course of follow-up and were therefore excluded from the analysis.…”
Section: Readmissionmentioning
confidence: 99%
“…Within EG group, 58% of participants reported that their previous gaming activities shortened their laparoscopic skills, which did not show statistical significance and the literature also has conflicting data when stating that video games shorten the curve. The biggest gain seems to be related to the psychomotor component [18][19][20][21] . It is known that the resting period is important for the retention of psychomotor skills as stated 22 .…”
Section: Discussionmentioning
confidence: 96%